Species-specific antimonial sensitivity in Leishmania is driven by post-transcriptional regulation of AQP1. - Goutam Mandal; Srotoswati Mandal; Mansi Sharma; Karen Santos Charret; Barbara Papadopoulou; Hiranmoy Bhattacharjee; Rita Mukhopadhyay (Public Library of Science (PLoS), 2015)
Leishmania is a digenetic protozoan parasite causing leishmaniasis in humans. The different clinical forms of leishmaniasis are caused by more than twenty species of Leishmania that are transmitted by nearly thirty species of phlebotomine sand flies. Pentavalent antimonials (such as Pentostam or Glucantime) are the first line drugs for treating leishmaniasis. Recent studies suggest that pentavalent antimony (Sb(V)) acts as a pro-drug, which is converted to the more active trivalent form (Sb(III)). However, sensitivity to trivalent antimony varies among different Leishmania species. In general, Leishmania species causing cutaneous leishmaniasis (CL) are more sensitive to Sb(III) than the species responsible for visceral leishmaniasis (VL). Leishmania aquaglyceroporin (AQP1) facilitates the adventitious passage of antimonite down a concentration gradient. In this study, we show that Leishmania species causing CL accumulate more antimonite, and therefore exhibit higher sensitivity to antimonials, than the species responsible for VL. This species-specific differential sensitivity to antimonite is directly proportional to the expression levels of AQP1 mRNA. We show that the stability of AQP1 mRNA in different Leishmania species is regulated by their respective 3'-untranslated regions. The differential regulation of AQP1 mRNA explains the distinct antimonial sensitivity of each species.